Out of court settlement of song and music litigations in Indonesia - Tanuatmaja, Hendra (Opción, 2019)
The aim of the study is to investigate out of court settlement ofsong and music litigations in Indonesia by making a Library Researchand adopting a descriptive normative approach. As a result,agreements dealing with the transfer of music copyright should containa provision on the option of making an amicable out-of-courtsettlement of disputes or through a dispute settlement mediationinstitution. In conclusion, it would be better if every agreement dealingwith the transfer of music copyright also contains a provision on theoption of making an amicable settlement of disputes through a disputesettlement mediation institution.